Mobile Feedback System For Improving Facilities In Utar Campus - Chong, Zi Ming (2020)
Although there is an existing feedback system in University Tunku Abdul Rahman to collect students’ feedbacks on the facilities, there are still some limitations on it. These limitations have caused the decreasing of students to give feedback on the facilities. In order to improve UTAR images, broken facilities should be reported and fixed on time. It is important that a good study environment can help students to enjoy their university life and improve their academic results. Therefore, a mobile feedback application is developed to identify problems with existing feedback system, helping students/academic staffs lodging complaints/feedback against the defects on facilities in the campus and displaying the feedback progress. With the implementations of the mobile application, the categories are listed and easy for students or academic staffs (reporters) to choose. All the progress of feedbacks reported will be tracked by reporters. Reporters will receive an email as a notification when the progress of the feedback is updated. Reporters will be able to give rating on the staff’s performance. For staffs, it provides a filtering function to filter out the feedbacks according to their progress. Admin of the mobile application can assign the feedbacks to any staffs and able to follow up the monthly feedbacks reported or updated and staffs’ performance. These features resolve the problems faced by reporters and helped admin to catch up the staffs’ performance and work easily.